Thermal technical properties of ecocotton/Ekovatos šiluminės techninės savybės - Gnip, Ivan; Keršulis, Vladislovas (Journal of Civil Engineering and Management, 1998)
The purpose of this investigation was to determine thermal technical properties of Ecocotton (or Ecofibre) – thermoinsulating material produced from waste newspaper, boric acid and borax and to evaluate the most optimal areas for application of this material on the basis of this investigation.The density, antiseptic and antipirene quantities of the samples were determined according to [2], thermal conductivity at 25 °C – [4], equilibrium sorbative moisture content – [5], vapour permeability – [6]. The dependencies of dry Ecocotton thermal conductivity on its density and moisture content are given in Figs 1 and 2 as well as after mathematical statistical treatment using the regressive equations (1) and (2). These dependencies are linear. Ecocotton specific heat at 20–25 °C is 1040±100 J/kg · K.The determined equilibrium sorbative moisture content dependency on air relative humidity is given in Table 1 together with literature data about analogous Finnish material Selluvilla-SV. The difference between our and literature data is not significant.The vapour permeability results for Ecocotton are given in Table 2. This value is close to that for mineral wool products.The data about layeral and seasonal distribution of moisture content in Ecocotton and analogous Finnish product Selluvilla-SV used for insulating of attic floors are given in Tables 3, 4 and Fig 3. It was proved on the basis of these results and equilibrium moisture content calculations of building enclosures with insulating layer of Ecocotton, that the calculated equilibrium moisture content of Ecocotton is 9% (to mass). The calculated thermal conductivity and heat capacity coefficients of Ecocotton were calculated according to formulas (3) and (4). Experimental (specific heat C( ), kJ/kg · K: thermal conductivity λ(), W/m · K) and calculated (weight moisture content Ws %; thermal conductivity λ, W/m·K; heat capacity coefficient S, W/m2K; vapour permeability μl, mg/m·h·Pa) thermal technical values for 35, 50 and 75 kg/m3 density Ecocotton are given in Table 5. The most optimal areas for application of Ecocotton are insulation of building enclosures with ventilated air space.Article in Lithuanian.First Published Online: 26 Jul 2012